PERAN LEMBAGA KEAGAMAAN DALAM MEMBINA KERUKUNAN UMAT BERAGAMA: STUDI KASUS PADA MAJELIS PANDITA BUDDHA MAITREYA KOTA BATAM: THE ROLE OF RELIGIOUS INSTITUTIONS IN PROMOTING RELIGIOUS HARMONY: A CASE STUDY OF MAJLIS PANDITA BUDDHA MAITREYA BATAM CITY - Novi Dwi Nugroho (Balai Penelitian dan Pengembangan Agama Jakarta, 2015)
This paper presents the results of research on the role of Majlis Pandita Buddha Maitreya (Mapanbumi) Batam. This research seeks to answer on how Mapanbumi’ views or attitudes toward religious harmony and what programs or activities that this majlis conduct concerning religious harmony. Using a case study model, data were collected through interviews, documents analysis, observations, and focus group discussions. The study found that according to Mapanbumi Batam, the religious harmony is something that has to be fought by all humans, regradless of race, ethnicity, culture, and religion, since all human beings are principally brothers. Mapanbumi Batam undertakes programs or activities in the field of inter- religious harmony through establishing public schools Maitreya Wira based on Buddhism Maitreya philosophy. This institution also run other social activities, including providing assistance to Al-Fateh rehabilitation institution, carrying out blood donation program, setting up vegetarian festival, and celebrating cultural and religious festivals which open to the public. Keywords: Religious Institutions, Mapanbumi, Harmony, the city of Batam, Buddha Tulisan ini menyajikan hasil penelitian mengenai peran Majelis Pandita Buddha Maitreya (Mapanbumi) Kota Batam. Penelitian ini hendak menjawab bagaimana pandangan atau sikap serta program atau kegiatan apa saja yang dilakukan oleh Mapanbumi Kota Batam mengenai kerukunan umat beragama. Dengan menggunakan model studi kasus, data penelitian digali mengguanakan metode wawancara, studi dokumen, observasi, dan kelompok diskusi terfokus. Penelitian ini mendapati, bahwa kerukunan umat beragama bagi Mapanbumi Kota Batam adalah hal yang harus diperjuangkan oleh semua manusia walaupun berbeda suku, etnis, budaya, dan agama, karena pada prinsipnya semua manusia adalah saudara. Program atau kegiatan yang dilakukan oleh Mapanbumi Kota Batam dalam bidang kerukunan antar umat beragama adalah dengan mendirikan sekolah Maitreya Wira yang berfalsafah Budhisme Maitreya, tapi terbuka untuk umum. Kegiatan sosial yang lain adalah dengan memberikan bantuan kepada panti rehabilitasi Al-Fateh, kegiatan donor darah, festival vegetarian, dan perayaan-perayaan hari besar yang terbuka untuk umum. Kata Kunci: Lembaga Keagamaan, Mapanbumi, Kerukunan, Kota Batam, BuddhaRe